Cyclophilin A and CD147 associate with progression of diabetic nephropathy. (2nd December 2018) - Chiu, Ping-Fang; Su, Shih-Li; Tsai, Chun-Chieh; Wu, Chia-Lin; Kuo, Chen-Ling; Kor, Chew-Teng; Chang, Chia-Chu; Liu, Chin-San
Abstract: To find the associations of circulating cyclophilin A (CyP A) and CD147/EMMPRIN with renal outcomes in type 2 diabetes patients and possible pathogenesis involved. Total 131 patients were recruited since 2004. Glycated hemoglobin, blood glucose and urine albumin–creatinine ratio levels at baseline and every 3 months were measured. Plasma CyP A and CD147 were also measured at baseline. Patients were divided into two groups based upon the median level of the baseline plasma CyP A value: < 93.64 ng/mL (group A, n = 65), ≥ 93.64 ng/mL (group B, n = 66). The estimated glomerular filtration rate was calculated at each follow-up visit. Besides, mitochondrial function assay by cellular mitochondrial energy utility was studied when cells were exposed to glucose or exogenous CyP A or both. Multivariate analysis, using median level (93.64) ng/mL as the cut-off value, revealed that circulating CyP A and CD147 levels at baseline were associated with the baseline estimated glomerular filtration rate (eGFR) ( p = .042 and p = .001 separately) in cross-sectional analysis. Longitudinally, higher baseline plasma CyP A level was also correlated to a rapid decline in eGFR ( p = .016). The results were also significant when using the continuous plasma CyP A level ( p = .003). In cells exposed to glucose, results of oxygen consumption rate (OCR) showed a significant reduction in basal respiration, maximal respiration and ATP production. Depressed OCR further occurred when incubated with both of CyP A and glucose. Plasma CyP A and CD147 can serve as indicators of renal disease progression in type 2 diabetes patients.